LOCAL CHARACTER OF THE STRESS-STRAIN STATE DURING LASER PROCESSING - Kharchenko, Volodymyr; Kindrachuk, Myroslav; Savchuk, Petro; Kostetskyi, Ivan; Hlovyn, Mykhailo (Problems of Friction and Wear, 2024)
The nature of the stress state arising under sliding friction loading is investigated on the model of a discretely processed material in which there is an annular transition zone between the inclusions (hardened area) and the matrix according to the known law of change in its mechanical properties. It is shown that local stresses in the material, depending on the type of loading of the elementary volume, can be predicted and calculated, taking into account the mechanical properties, appearance, and structure of the transition zone that occurs as a result of laser processing. The strength of the transition zone has a linear dependence and the stress concentration in the area after laser treatment decreases and smoothly transitions to the matrix, and then it decreases to the stresses in the matrix, which gives the advantage of discrete laser treatment of hardened steel.